Pick-And-Place Mobile Autonomous Robots - Chan, Jaan Huan (Universiti Sains Malaysia, 2005)
This thesis presents a Research and Development study on building Pick-and-Place Mobile Autonomous Robot (MARS). It considers various steps and criteria during the study. This project is mainly regarding on designing and fabricating an autonomous robot which posses the functions such as line tracking, sense section radius of the Canister, feed in the Rubber Balls, etc. This robot is designed (in the size of 500mm x 500mm x 1500mm before the game start and limited 2000mm in height after the game start) to accomplish tasks which are tracks through the game field, reaches the Main Torch, rotates the Main Torch and finally feed the Rubber Balls into the Canister. By applying Quality Function Deployment (QFD), robot was successfully designed from the several alternatives. It was designed to be detachable to form two robots named as EX-Transporter and Feeder-EX. According to their tasks, control systems were built to enhance the efficiency of the robots. However, several tests were conducted to ensure their reliability, such as tracking test, straightness test, robot stabilizing system test, defending system test, robot extending system test, radius sensing system test and Rubber Balls feeding system test. As a result, these robots achieve a good performance through the tests. However, it is recommended that, elastic strings which were used to replace the complex mechanism needed to be changed after three times of usage to ensure its functionality.